Characteristic of stress evolution on fault surface and coal bursts mechanism during the extraction of longwall face in Yima mining area, China. (July 2020) - Wang, Hongwei; Shi, Ruiming; Deng, Daixin; Jiang, Yaodong; Wang, Gang; Gong, Weili
Abstract: Due to strain energy releases sharply, fault slip is often accompanied with sudden stress change around fault structures, especially on the fault surface. In this study, the slippage of a reverse fault structure induced by coal mining in Yima mining area, Henan province, China is studied by employing physical and numerical simulation. The stress evolution around this fault is analyzed to further understand the mechanism of coal bursts around the fault structures. The results show that the normal stress is relatively greater than shear stress on the fault surface, and the normal and shear stress on the fault surface near the coal seam are greater than that far away from the coal seam. It is interesting to find that the variation of normal stress and shear stress on the middle of fault is opposite in the physical model. To in-depth understand this phenomenon, the numerical simulation method is employed to investigate the stress variation and dynamic energy evolution on the fault surface before, during and after fault slip by applied different horizontal stress on the lateral surface of model. The results show that the opposite variation of normal and shear stress is induced by the greater horizontal stress. This phenomenon can be considered as a precursory information for major fault slip. The horizontal stress is the main driving force of the fault slip induced by the coal seam mining. In this study, it is also suggested that the existence of extra-thick conglomerate rock and reverse fault in the high horizontal stress environment could cause large area of roof movement and provide the dynamic pressure source for the occurrence of coal bursts in Yima mining area. Highlights: The reason why the horizontal loading is the main driving force of the fault slip has been found out. The fault slip precursory information in terms of fault stress is found out. The dynamic environment of coal bursts from combined effect of extra-thick rock and F16 fault is studied. The reason why the coal burst accidents occur so frequently in Yima mining area is analyzed.